Criminal Liability and the Non Punishment Principle for Trafficking Victims in Indonesia - Natalia; Widagdo, Setyo; Istiqomah, Milda; Puspitawati, Dhiana (Jurnal IUS Kajian Hukum dan Keadilan, 2026)
The non-punishment principle for trafficking victims is recognized in Article 18 of Law Number 21 of 2007 on the Eradication of the Crime of Trafficking in Persons, which stipulates that victims who commit criminal acts as a result of coercion by traffickers shall not be subject to punishment. However, this provision does not clearly define the doctrinal parameters of coercion, nor does it explain how criminal liability should be assessed when an unlawful act is committed within conditions of exploitation, dependence, intimidation, or constrained autonomy. This article examines the relationship between criminal liability and the non-punishment principle for trafficking victims in Indonesia. It employs normative legal research by analyzing statutory regulations, criminal law doctrine, international instruments, and relevant scholarly literature. The study finds that the non-punishment principle should not be understood merely as a procedural exemption from punishment, but rather as a doctrinal mechanism for excluding culpability where the victim’s conduct is directly connected to trafficking-related coercion. It further argues that Indonesian law requires a more clearly articulated framework for assessing coercion, including the causal relationship between trafficking and the offense, the degree of the victim’s constrained autonomy, and the evidentiary burden borne by victims. The contribution of this article lies in proposing a more precise doctrinal approach to distinguishing punishable conduct from victimization-driven conduct in trafficking cases, thereby ensuring that Article 18 functions as an effective instrument of victim protection rather than a formal guarantee that remains difficult to implement in practice.